Non‐invasive prenatal screening for fetal triploidy using single nucleotide polymorphism‐based testing: Differential diagnosis and clinical management in cases showing an extra haplotype. (21st May 2022) - Kantor, Valerie; Jelsema, Russ; Xu, Wenbo; DiNonno, Wendy; Young, Kathryn; Demko, Zachary; Benn, Peter
Abstract: Objective: An extra haplotype is infrequently encountered in single nucleotide polymorphism(SNP)‐based non‐invasive prenatal testing (NIPT) and is usually attributed to an undetected twin or triploidy. We reviewed a large series to establish relative frequencies of these outcomes and identify alternative causes. Methods: In 515, 804 women receiving NIPT from September 2017 through March 2019, all results with an extra haplotype were reviewed. Known viable and vanished twin pregnancies were excluded. For positive cases, pregnancy outcome information was sought. Results: Of 1005 results with an extra haplotype (1 in 513), pregnancy outcome was available for 773 cases: 11% were confirmed or suspected triploidy; 65% to vanished twin; 10% with pregnancy loss. Rare explanations included complete mole, chimera, undisclosed donor egg pregnancy, maternal organ transplant and one instance of maternal neoplasm. Among triploid cases that were detected and independently confirmed, 23/27 (85%) were diandric. Conclusion: SNP‐based NIPT, with detection of an extra haplotype, is 11% predictive of triploidy. For results with an extra haplotype, ultrasound is recommended to establish viability, evaluate for twins (viable or vanished), and detect findings consistent with triploidy. Review of patient history, serum screening, and ultrasound will reduce the number of CVS or amniocenteses necessary to confirm a diagnosis of triploidy. Key points: What's already known about this topic? Both digynic and diandric triploidy are occasionally seen in pregnancies but are extremely rare in live‐births In cell‐free DNA prenatal screening, the presence of an extra haplotype could be indicative of either twin pregnancy or triploidy What does this study add? Outcomes for a large series of prenatal screening tests where an extra haplotype was identified in cell‐free DNA Complete moles, chimeras, transplantation, and donor egg are additional explanations for extra haplotypes We discuss prenatal management when an extra haplotype is observed in cell‐free DNA